(untitled) (European journal of volunteering and community-based projects, 2026)
Purpose: Provide a definition of a smart hospital and identify the key digital technologies that must be adopted to guide hospitals toward e-health 4.0. The concept of a smart hospital has not been rigorously defined in the literature, and there is no widely accepted definition. This research aims to fill this gap by identifying the attributes of a smart hospital and proposing a definition based on these. Methods: A qualitative case study methodology was used to study smart hospitals. The focus was on two Italian hospitals: one public and one private, considered best performers according to the smart health rankings developed by the international weekly magazine Newsweek, in collaboration with the research firm Statista. Primary data was collected using semi-structured questionnaires aimed at healthcare professionals, while secondary data was obtained from official documentation, websites, press releases and institutional reports. Findings: Following the review of e-health and smart hospitals, it was found that there is no single model of a smart or intelligent hospital, and that the evolution of these two institutions in this direction is closely linked to the digital technologies used. Originality: To fully realize the true potential of the smart hospital, it is essential to consider digital technologies not as separate entities, as they must interact to optimize healthcare processes and improve the quality of care. In the light of this, a framework has been developed that highlights the most widespread digital technologies that must be integrated into medical treatments and administrative processes to support the transition from a traditional to a smart hospital.